Question:
Solution:
Consider the following functions:
![f(x)\text{ = x+4}](https://img.qammunity.org/2023/formulas/mathematics/high-school/y0gc2f4asribn7dd99aaeq1fedtcc7tigf.png)
![g(x)\text{ = }4x-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/8k94le3rqfa6bkb1gwme75tr7vow028yqe.png)
then:
![(f\circ g)(x)\text{ = f(g(x))= (4x-3)+4}](https://img.qammunity.org/2023/formulas/mathematics/high-school/37d6vpc8x3ch2pq045dj87w6aozkvg3wwe.png)
this is equivalent to:
![(f\circ g)(x)\text{ =(4x-3)+4 = 4x +1}](https://img.qammunity.org/2023/formulas/mathematics/high-school/zye63ilhatloot283e6mw7wffroiug06dc.png)
thus:
![(f\circ g)(x)\text{ =4x +1}](https://img.qammunity.org/2023/formulas/mathematics/high-school/12iy85qqs7fayozg9j4n39tuhi4o4hgs5p.png)
So, replacing x = 2 in the previous function we get:
![(f\circ g)(2)\text{ =4(2) +1 = 9}](https://img.qammunity.org/2023/formulas/mathematics/high-school/9vfxwxxagqo4yh4p936byhmsben3iu6wxe.png)
then:
![(f\circ g)(2)\text{ = 9}](https://img.qammunity.org/2023/formulas/mathematics/high-school/svtmz4sbeo49k06pbygx4lhsj8x1nryfo5.png)
On the other hand, the composition:
![(g\circ f)(x)\text{ = g(f(x)) = 4(x+4)-3}](https://img.qammunity.org/2023/formulas/mathematics/high-school/4ifgtnmcniftkkmnkvg1z0otevartn0z7v.png)
this is equivalent to:
![(g\circ f)(x)\text{ = 4(x+4)-3 = 4x +16-3 = 4x - 13}](https://img.qammunity.org/2023/formulas/mathematics/high-school/c8eh6m55nb6iv30ms2phbjqzpvygjw4gf1.png)
then, we can conclude that:
![(g\circ f)(x)\text{ =4x - 13}](https://img.qammunity.org/2023/formulas/mathematics/high-school/xv6n9w75k2sw9wtkxezlywrco2dfmiwh85.png)
So, replacing x = 2 in the previous function we get:
![(g\circ f)(2)\text{ =4(2) - 13 = 8-13 = -5}](https://img.qammunity.org/2023/formulas/mathematics/high-school/49to4ydhu4uzudf8mvc0avceeb9vl3evvt.png)
then:
![(g\circ f)(2)\text{ =4(2) - 13 = 8-13 = -5}](https://img.qammunity.org/2023/formulas/mathematics/high-school/49to4ydhu4uzudf8mvc0avceeb9vl3evvt.png)
then:
![(g\circ f)(2)\text{ =-5}](https://img.qammunity.org/2023/formulas/mathematics/high-school/uqcblt2ctclnzokqkuj2yp06ryxgmzll93.png)
Then the correct answers are:
1)
![(f\circ g)(x)\text{ =4x +1}](https://img.qammunity.org/2023/formulas/mathematics/high-school/12iy85qqs7fayozg9j4n39tuhi4o4hgs5p.png)
2)
![(f\circ g)(2)\text{ = 9}](https://img.qammunity.org/2023/formulas/mathematics/high-school/svtmz4sbeo49k06pbygx4lhsj8x1nryfo5.png)
3)
![(g\circ f)(x)\text{ =4x - 13}](https://img.qammunity.org/2023/formulas/mathematics/high-school/xv6n9w75k2sw9wtkxezlywrco2dfmiwh85.png)
4)
![(g\circ f)(2)\text{ =-5}](https://img.qammunity.org/2023/formulas/mathematics/high-school/uqcblt2ctclnzokqkuj2yp06ryxgmzll93.png)